La importancia de la Economía de la Felicidad: análisis de la situación actual y perspectivas a futuro - Agustín Coll, Sandra Maceri (2023)
The main objective of this work was to analyze the different discoveries obtained by the Economy of Happiness in recent decades in order to contextualize them in the postpandemic global context. In view of this new global scenario, we sought to give the reasons why the Economy of Happiness should have an even more active and preponderant role, rethinking the field. The current situation of the Economy of Happiness and future perspectives were examined, as well as what measures can be carried out to improve happiness indices in society. The methodology used was of an analytical conceptual nature. The different conclusions obtained by the Economics of Happiness were reviewed, taking into account the different statistical and descriptive results of the discipline. The work was divided into three parts, observing the need for action in the state, business and educational spheres, explaining the need for happiness to have a more preponderant role in these areas and evaluating how they could carry it out, as well as the benefits that these sectors in particular and society as a whole would obtain. The results obtained showed that, in this new scenario, the Economy of Happiness has the opportunity and the need to become more important than ever, something that will be beneficial for all those involved.